2016
DOI: 10.1159/000448799
|View full text |Cite
|
Sign up to set email alerts
|

Single-Tube Flow Cytometry Assay for the Detection of Mature Lymphoid Neoplasms in Paucicellular Samples

Abstract: Objectives: Flow cytometry (FC) has become a useful support for cytomorphologic evaluation (CM) of fine-needle aspirates (FNA) and serous cavity effusions (SCE) in cases of suspected non-Hodgkin lymphoma (NHL). FC results may be hampered by the scarce viability and low cellularity of the specimens. Study Design: We developed a single-tube FC assay (STA) that included 10 antibodies cocktailed in 8-color labeling, a cell viability dye, and a logical gating strategy to detect NHL in hypocellular samples. The resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Stacchini et al 7 observed CD4:CD8 ratios with ranges of 0.1‐1.7 and 0.8‐4.4 in cases of reactive hyperplasia and metastasis, respectively. Three cases of Hodgkin lymphoma exhibited a CD4:CD8 ratio ranging from 3.9‐7.3 in their study.…”
Section: Discussionmentioning
confidence: 99%
“…Stacchini et al 7 observed CD4:CD8 ratios with ranges of 0.1‐1.7 and 0.8‐4.4 in cases of reactive hyperplasia and metastasis, respectively. Three cases of Hodgkin lymphoma exhibited a CD4:CD8 ratio ranging from 3.9‐7.3 in their study.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies showed that FNC is suitable for different molecular procedures and LN FNC-FC plays a key role in guaranteeing the best management of the available material. The article by Peluso et al [19] describes the most common molecular procedures used for NHL and their potential application on FNC material, and the article by Stacchini et al [20] focuses on small samples and specific technical solutions. In conclusion, the six features highlighted by Calvino identify qualities shared by FC, which can be fully exploited in the diagnosis of LN-FNC and represent the basis for the application of specific molecular procedures.…”
Section: Figmentioning
confidence: 99%